Evaluation of Information System Effectiveness Level Using COBIT Framework 5 - Budi Hartono Mesa; Johanes Fernandes Andry (CogITo Smart Journal, 2018)
PT XYZ Expo is a company engaged in the MICE industry (Meeting, Incentive, Conference, and Exhibition). The company has implemented an information system to facilitate the process of leasing building. Problems that have occurred in the operational activities is a discrepancy between the stocks of physical goods with the stock in the system. Audit information system is conducted to find out how the company coordinate operational activities and manages the existing problems through the evaluating the effectiveness level of information systems. The research starting from observation, then identify problem and collecting data, then determine the domain that will be used in interview, after conducting interview the author do analysis and also calculate capability level, last the author give a report and recommendation for feedback. This research uses capability model in framework COBIT 5 to measure capability level in each process. This study focuses on the process of DSS01 and DSS03. Based on this research, it was found that the sub-domains of DSS01 and DSS03 were at 2.4. The conclusion obtained from the level of capability level is PT. XYZ Expo has been running well and effective but still needs to make some improvements to improve the capability level.